(untitled) (Heteroglossia – studia kulturoznawczo-filologiczne, 2025)
Dave Eggers’ memoir, A Heartbreaking Work of Staggering Genius, is celebrated for its elements of metamodernism, but existing scholarship overlooks its central theme of the ethics of care as a guiding principle in personal and wider social relationships. This paper explores how Eggers’ protagonist Dave embodies the key tenets of the ethics of care, including attentiveness, responsiveness, responsibility and respect for autonomy. Drawing on the work of care ethicists such as Carol Gilligan, Nel Noddings and Virginia Held, the analysis highlights the interplay of emotions and moral dilemmas in caregiving. Through Dave’s relationships with his terminally ill mother, younger brother, and friends, the memoir reveals the complexities of caregiving, including the tensions between paternalism and autonomy, emotional attachment, and rationality. In addition, Dave’s experiences inspire a politicized vision of care, encapsulated in his concept of ‘The Lattice’,” which extends care beyond familial boundaries and advocates for collective social responsibility. This study positions A Heartbreaking Work of Staggering Genius as a profound exploration of care ethics, offering a nuanced understanding of its foundations in metamodernism and emotional depth.